CORONAVIRUS IN WATERFOWL - Núñez Nogueira, Gabriel (Kuxulkab', 2020)
Coronaviruses are pathogens recognized for their animal origin and commonly associated with terrestrial environments and animals, particularly mammals and birds. Within them, there are reports of their presence in aquatic birds, which appear to be the main group in carrying and circulating this type of virus in healthy populations and play an important role in the presence in such type of environments. Although the route of infection for COVID-19 by this route, has not been demonstrated to date, there are cases of other respiratory viral infections, which are known to have become transferred to humans, from birds. Ducks, cormorants, herons, ties, gulls, among others, have shown to be carriers of COVs, being SARS-CoV present in ducks and geese.
Keywords: Coronavirus; Waterfowl; SARS; Ducks; Geese